Thermal Annealing Effect of Strontium Stannate Thin Film Grown by an RF Magnetron Sputtering - Yusmar Palapa Wijaya; Fatin Nor Ahmad; Khairul Anuar Mohamad (International ABEC, 2021)
Strontium Stannate (SrSnO3 or SSO) thin films were deposited on the ITO substrate using an RF magnetron sputtering method. Thermal annealing has been treated to the samples by 400oC, 600oC and 800oC using a furnace. Structure evolution has been observed by X-Ray diffraction (XRD), atomic force microscopy (AFM) and ultraviolet visible (UVVIS). A decrease full width at half maximum (FWHM) at (002) peak observed. The amplitude’s reduction from 0.472 to 0.354 for as deposited and as annealed sample, respectively, indicating an improvement of crystallite size by 30%. Furthermore, an absorbed wavelength by transmittance exhibited at 380 nm and 600 nm. The energy bandgap of the annealed thin film at 400oC, 600oC and 800oC were 3.33 eV, 3.28 eV and 3.20 eV, respectively.